2011
DOI: 10.1093/brain/awr184
|View full text |Cite
|
Sign up to set email alerts
|

Genetic spectrum of hereditary neuropathies with onset in the first year of life

Abstract: Early onset hereditary motor and sensory neuropathies are rare disorders encompassing congenital hypomyelinating neuropathy with disease onset in the direct post-natal period and Dejerine–Sottas neuropathy starting in infancy. The clinical spectrum, however, reaches beyond the boundaries of these two historically defined disease entities. De novo dominant mutations in PMP22, MPZ and EGR2 are known to be a typical cause of very early onset hereditary neuropathies. In addition, mutations in several other dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(130 citation statements)
references
References 47 publications
3
117
0
6
Order By: Relevance
“…Data from recent studies in large cohorts of CMT patients indicated that molecular diagnosis could be established in ϳ 50-70% of them [Baets et al, 2011;Saporta et al, 2011]. These results strongly indicate that an important number of additional CMT genes remains to be discovered.…”
Section: Ngs and Cmt: Perspectivesmentioning
confidence: 94%
“…Data from recent studies in large cohorts of CMT patients indicated that molecular diagnosis could be established in ϳ 50-70% of them [Baets et al, 2011;Saporta et al, 2011]. These results strongly indicate that an important number of additional CMT genes remains to be discovered.…”
Section: Ngs and Cmt: Perspectivesmentioning
confidence: 94%
“…As a whole, NEFL mutations represent between 0.8 and 2 % of all patients with CMT [15,18,[22][23][24][25]. NEFL-associated CMT is a highly variable disorder that comprises more than 18 disease-causing mutations, targeting the head or rod protein domains, with highly variable phenotypic expression, N98S (N97 in the old nomenclature) being reported in five pedigrees with severe early-onset disease phenotype [15,19,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…This finding has been considered as the pathological hallmark of CMT4B1 and CMT4B2. However, similar focally folded myelin sheaths were found, although to a lesser extent, in FGD4, PRX, MPZ, and SH3TC2 associated CMT [38][39][40]. Secondary axonal loss is usually observed in CMT4B1.…”
Section: Histopathologymentioning
confidence: 76%